2007
DOI: 10.1158/1078-0432.ccr-06-2149
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the Mismatch Repair Protein MSH6 in Human Glioblastomas Is Associated with Tumor Progression during Temozolomide Treatment

Abstract: Purpose: Glioblastomas are treated by surgical resection followed by radiotherapy [X-ray therapy (XRT)] and the alkylating chemotherapeutic agent temozolomide. Recently, inactivating mutations in the mismatch repair gene MSH6 were identified in two glioblastomas recurrent post-temozolomide. Because mismatch repair pathway inactivation is a known mediator of alkylator resistance in vitro, these findings suggested that MSH6 inactivation was causally linked to these two recurrences. However, the extent of involve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
249
3
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 391 publications
(283 citation statements)
references
References 31 publications
14
249
3
6
Order By: Relevance
“…Recent research confirmed loss of MMR protein hMSH6 in human glioblastomas associated with tumor progression during TMZ treatment, as well as demonstrating hMSH6 loss during TMZ treatment regardless of MGMT status [38,47]. Our data are consistent with clinical observations reporting hMSH6 loss as one phenotype acquired in glioma patients treated with TMZ.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Recent research confirmed loss of MMR protein hMSH6 in human glioblastomas associated with tumor progression during TMZ treatment, as well as demonstrating hMSH6 loss during TMZ treatment regardless of MGMT status [38,47]. Our data are consistent with clinical observations reporting hMSH6 loss as one phenotype acquired in glioma patients treated with TMZ.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, impaired MMR through loss of hMSH6 expression and enhanced expression of a key BER gene developed in SNB19VR cells. Our observations parallel in vitro and clinical studies reporting that alkylator resistance can be mediated either by MGMT over-expression or MMR deficiency [34,38,47]. Because tumors readily acquire the ability to repair or tolerate TMZ-induced lesions, treatment is rendered ineffective.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…10,11 This suggests that additional mechanisms are involved in tumor resistance to 12 Thus, resistance of GBM cells to TMZ includes various events, such as loss of the phosphatase and tensin homolog (PTEN), leading to the activation of the phosphoinositide-3-kinase (PI3K)/Akt pathway, deficiency in the DNA mismatch repair system, mutations in the pro-apoptotic p53 protein, overexpression of the anti-apoptotic protein Bcl-2, or the selection of less-differentiated pre-existing resistant cells in the parental tumor. [13][14][15][16][17][18][19] Dysregulation of the expression of microRNAs (miRNAs) is emerging as an important step in early processes during tumorigenesis as well as disease progression/metastasis in various malignancies including GBMs. [20][21][22] The miRNAs function mainly through their ability to bind to the 3â€Č untranslated regions of mRNAs, leading to their degradation or suppression of their translation.…”
Section: Introductionmentioning
confidence: 99%
“…Given the negative clinical impact of acquired resistance, GBM cell lines were generated possessing acquired resistance to TMZ [20]. Molecular mechanisms of resistance to TMZ in vitro were identified, MMR loss and MGMT upregulation, consistent with acquired resistance, emerging clinically during TMZ treatment and tumor progression [21,22,23]. In this paper, we advance the possibility that imidazotetrazines structurally related to TMZ but with different N-3 monofunctional alkylation potential might generate cytotoxic lesions in DNA which would not be repaired by MGMT and would be unaffected by MMR status.…”
Section: Introductionmentioning
confidence: 99%